Expanding Europe’s conflicts-law constitution: against negative externalities of dominant function systems - Gunther Teubner (European Law Open)
Why should one expand Christian Joerges’s pioneering concept of ‘Europe’s conflicts-law constitution’? The European constitution should consistently incorporate the double plurality of Europe because, for centuries, Europe has been governed by two powerful pluralities that are orthogonal to each other, but at the same time closely interpenetrate each other. Europe’s material constitution is characterised not only by the conflicts between nation-state policies, but also by the deeper conflicts between different intrinsic normativities of societal institutions.